The Relationship Between Number of Medications and Weight Loss or Impaired Balance in Older Adults - Agostini, Joseph V.; Han, Ling; Tinetti, Mary E. (Journal of the American Geriatrics Society (JAGS), 2004)
Objectives: To examine the relationship between cumulative medication exposure and risk of two common manifestations of adverse drug effects: weight loss and impaired balance. Design: Cross‐sectional and longitudinal cohort. Setting: Urban Connecticut community. Participants: Eight hundred eighty‐five community‐dwelling residents aged 72 and older. Measurements: Weight loss (≥10 pounds) and balance, a composite of four balance measures. Results: Participants took a mean±standard deviation of 2.2±1.9 medications (range 0–15). After adjustment for age, depressive symptoms, cognitive impairment, vision and hearing impairments, number of chronic diseases, and number of hospitalizations in the previous year, the adjusted odds ratio (OR) for weight loss was 1.48 (95% confidence interval (CI)=0.85–2.59) for those taking one to two medications, 1.96 (95% CI=1.08–3.54) for three to four medications, and 2.78 (95% CI=1.38–5.60) for five or more medications. For impaired balance, adjusted ORs were 1.44 (95% CI=0.94–2.19), 1.72 (95% CI=1.09–2.71), and 1.80 (95% CI=1.02–3.19), respectively. Conclusion: A greater number of medications were associated with increased risk of adverse drug outcomes, after extensive adjustment for chronic illness. Clinicians should consider the adverse effects of total drug use and not merely the benefits or risks of individual medications for specific diseases.